Formation of ecological and geographical world outlook in learning geography - Svetlana I. Beketova; Ilgizar T. Gaisin; Elena I. Vlasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article focuses on the role of school geography course in the implementation of the main goals of education, the formation of well-rounded personality with modern worldviews. It is shown that the purpose of the study of geography in learning the system of geographical knowledge as a component of the scientific world.Disclosed issues of formation of ecological and geographical world as part of the scientific worldview, its structural components: knowledge, ideas, attitudes, beliefs, values. The stages of the formation of the geographical picture of the world: in V-VI classes - an understanding of the world picture, in the VII class - the integrity of the picture of the world, in the VIII class - a picture of Russia as a part of the world, in the IX class - a picture of the socio-economic structure of Russia, in X-XI classes - the picture of social and economic structure of the world. Marked by the principles of continuity and system, the principle of local lore, which needed for the formation of a scientific outlook. Highlight and presents a system of ecological and geographical concepts, like the concepts of environmental and socio-ecological concepts from V to X-XI classes. We consider the research activity of schoolchildren and the formation of philosophical views and beliefs at the time of its execution. Gave an examples of scientific search of student's work submitted for research readings interregional youth readings behalf Kayum Nasyyri and in scientific-practical conferences devoted to geography and local history of activity research.